Evaluation of palate area before and after rapid maxillary expansion, using cone-beam computed tomography - Bruder,Carolina (2019)
ABSTRACT Objective: The aim of this study was to estimate the changes in the palate area after rapid maxillary expansion (RME) with the Hyrax expander in growing subjects, using cone beam computed tomography (CBCT). Methods: Fourteen patients (9 girls and 5 boys; mean age = 11.7 ± 2.4 years) who required RME as part of their orthodontic treatment were included in this study. CBCT records had been taken before RME treatment (T0), at the end of active expansion (T1) and after a 6-month retention period (T2). The CBCT scans were manipulated with Dolphin Imaging® version 11.7 Premium software, in which landmarks were positioned and measured in relation to sagittal, coronal and axial planes, to verify the palate surface area. In addition, linear measurements of the palatal depth and width were assessed. These measurements were compared by using analysis of variance (ANOVA) for repeated measures. A p-value smaller than 0.05 was considered statistically significant. Results: The palatal surface area and width significantly increased from T0 to T1, respectively by 9.27% and 9.71%, and both decreased in a non-significant manner from T1 to T2. The palatal depth had non-significant differences at T0, T1 and T2. Conclusions: RME promotes a significant gain in the surface area of the palate and an increase in intermolar width. The Hyrax appliance was effective for the treatment of maxillary atresia in growing patients. There was no vertical alteration of the palate. After a 6-month retention period, the maxilla transverse dimension and the surface area of the palate remained stable.